2012
DOI: 10.1302/0301-620x.94b5.28247
|View full text |Cite
|
Sign up to set email alerts
|

Increasing stability by pre-bending the nails in elastic stable intramedullary nailing

Abstract: Elastic stable intramedullary nailing (ESIN) is generally acknowledged to be the treatment of choice for displaced diaphyseal femoral fractures in children over the age of three years, although complication rates of up to 50% are described. Pre-bending the nails is recommended, but there are no published data to support this. Using synthetic bones and a standardised simulated fracture, we performed biomechanical testing to determine the influence on the stability of the fracture of pre-bending the nails before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…However, because of the high repeatability due to minimal inter-individual variability [40-42], it was used successfully in previous biomechanical studies [23,26,27]. Furthermore, due to the configuration of the synthetic bone model, the nails could not be placed as proximally as is ideal in real operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the high repeatability due to minimal inter-individual variability [40-42], it was used successfully in previous biomechanical studies [23,26,27]. Furthermore, due to the configuration of the synthetic bone model, the nails could not be placed as proximally as is ideal in real operations.…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical in-vitro setting is described in detail elsewhere [23,26,27]. Each mid-shaft fracture was identically sawed by Sawbones® with a fracture length of 100 mm and an identical spiral fracture from distal lateral rotating to cranial medial (AO pediatric comprehensive classification of long bone fractures: 32D51 [28]; LiLa classification for pediatric long-bone fractures: 3.2.s.3.2.…”
Section: Methodsmentioning
confidence: 99%
“…Temporary implants for osteosynthesis require good ductility for geometrical adaption by the surgeon [32]. In-vitro and animal studies also show each alloy to possess good cytocompatibility [5,8].…”
Section: Stress Corrosion Cracking Of Magnesium Alloy Implantsmentioning
confidence: 99%
“…24 With our recently developed validated long spiral femur fracture model, we found advantages of steel over titanium nails 24 and demonstrated that using endcaps did not improve the stability of the ESIN-osteosynthesis, especially not in axial compression in a spiral fracture model. 25 Also, we proved the importance of prebending the nails of more than 30 degrees 26 and showed that an additional third nail reduced the risk of shortening and recurvation in the biomechanical model. 27 The transfer of this biomechanical results into clinical practice demonstrated that a third nail increases the stability of the fixation in a femoral fracture if the implantation and the prebending of the third nail is appropriate to the individual character of the fracture.…”
Section: Introductionmentioning
confidence: 69%